Overdentures on implants placed in bone augmented with fresh frozen bone - Rigo Leone; Viscioni Alessandro; Franco Maurizio; Guidi Riccardo; Strohmenger Laura; Brunelli Giorgio; Carinci Francesco (Serbian Medical Society - Dental Section, Belgrade, 2009)
Introduction In the last decade several studies have been performed to evaluate the clinical outcome of one or two stage loaded implants supporting overdentures. Aim Since fresh frozen bone (FFB) has an ever-increasing number of clinical applications and few reports are available on implants inserted into FFB, we performed a retrospective study on fixtures inserted in FFB and bearing overdentures. Methods In the period between December 2003 and December 2006, 17 patients (14 females and 3 males with a median age of about 56 years) were grafted and 60 implants inserted thereafter. A total of 17 overdentures were delivered: 8 in the mandible and 9 in the maxilla. Multiple implant systems were used: 22 Double etched, 7 SLA, 9 Anodic oxidized, and 22 CaPo4 ceramic-blasted. Implant diameter ranged from 3.25 to 4.3 mm and length from 11.5 to 16.0 mm. Implants were inserted to replace 23 incisors, 9 cuspids, 20 premolars and 8 molars. Results No implants were lost (i.e. survival rate = 100%) and no differences were detected among the studied variables. Kaplan Meier algorithm and Cox regression did not reveal any statistical differences among the studied variables also as regards the success rate. Conclusion Implants inserted FFB and bearing overdentures have a high survival rate and success rates, which are comparable to those of implants inserted in non-grafted bone. FFB bone is a reliable material for alveolar ridge augmentation. No difference was detected among removable prostheses supported by 2 or more implants.